A to Z of learning outside the classroom - Grigg, Russell; Lewis, Helen (London, England, UK : Bloomsbury Education, 2016)
"The A-Z of learning outside the classroom provides more than a thousand cross-curricular ideas, from making the most of the school grounds to visiting castles, farms and theatres... Drawing on academic research, the authors explain why learning outside the classroom is so beneficial to children, including special sections on how literacy and numeracy skills can be developed in real life contexts..."--Publisher description.
Cover -- Half-title -- Title -- Copyright -- Contents -- Acknowledgements -- Introduction -- Part 1: Questions -- What is the nature and scope of out-of-class learning? -- Why is out-of-class learning important? -- What theories underpin out-of-class learning? -- What contribution can out-of-class experiences make to the teaching of literacy, numeracy and the wider curriculum? -- What are the practical things to consider? -- How do we evaluate out-of-class provision? -- Conclusion -- Part 2: A-Z entries -- A is for Allotments -- B is for Beaches -- C is for Castles -- D is for Dens -- E is for Environmental centres -- F is for Farms -- G is for Galleries -- H is for Home learning environments -- I is for Islands -- J is for Jungles -- K is for Kitchens -- L is for Libraries -- M is for Museums -- N is for Neighbourhood -- O is for Observatories and planetariums -- P is for Ponds -- Q is for Quiet places -- R is for Rivers -- S is for Shops -- T is for Theatres -- U is for Underground -- V is for Virtual Learning Environments (VLEs) -- W is for Worship, places of -- X is for X marks the spot -- Y is for Yards -- Z is for Zoos -- Appendices -- References.
Includes bibliographical references.
CoED
Text in English
Keywords: Outdoor education